A meta-analysis on the efficacy and safety of St John's wort extract in depression therapy in comparison with selective serotonin reuptake inhibitors in adults - Cui Y; Zheng Y (Neuropsychiatric Disease and Treatment)
Yong-hua Cui,1 Yi Zheng1,2 1Department of Pediatrics, Beijing An’ding Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Institutes of Brain Disorders, Beijing, People’s Republic of China Objective: The aim of the study was to investigate the efficacy and safety of St John’s wort extract and selective serotonin reuptake inhibitors (SSRIs) in the treatment of depression.Methods: Databases were searched for studies comparing efficacy and/or safety of St John’s wort extract with SSRIs in depression from 1966 to April 2015. Stata software was used for statistical analysis.Results: Twenty-seven studies met the study entry criteria. A total of 3,126 patients with depression were included. St John’s wort extract did not differ from SSRIs in clinical response, remission, and mean reduction in Hamilton Rating Scale for Depression score. St John’s wort extract had a significantly lower rate of adverse events compared to SSRIs (summary relative risk: 0.77; 95% confidence interval: 0.70, 0.84, P=0.00) and had fewer withdrawals due to adverse events. St John’s wort extract had superior safety in the management of patients with depression.Conclusion: Both St John’s wort extract and SSRIs are effective in treating mild-to-moderate depression. St John’s wort extract is safer than SSRIs. Keywords: St John’s wort, selective serotonin reuptake inhibitors, depression, meta-analysis